2021
DOI: 10.1093/rb/rbab045
|View full text |Cite|
|
Sign up to set email alerts
|

Combination of graphene oxide and platelet-rich plasma improves tendon–bone healing in a rabbit model of supraspinatus tendon reconstruction

Abstract: The treatment of rotator cuff tear is one of the major challenges for orthopedic surgeons. The key to treatment is the reconstruction of the tendon-bone interface (TBI). Autologous platelet-rich plasma (PRP) is used as a therapeutic agent to accelerate the healing of tendons, as it contains a variety of growth factors (GFs) and is easy to prepare. Graphene oxide (GO) is known to improve the physical properties of biomaterials and promote tissue repair. In this study, PRP gels containing various concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…For tensile testing, the specimen was placed on a material testing system (AG–X 10 kN, Shimadzu, Japan). The sample was fixed into the machine in the anatomical posture to allow the tensile loading of the tendon in the anatomical direction [1]. The specific tensile steps were as follows: (a) preconditioning: each specimen was first preconditioned with a tensile force of 5 N. The tensile cycle lasted 15 s and was performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…For tensile testing, the specimen was placed on a material testing system (AG–X 10 kN, Shimadzu, Japan). The sample was fixed into the machine in the anatomical posture to allow the tensile loading of the tendon in the anatomical direction [1]. The specific tensile steps were as follows: (a) preconditioning: each specimen was first preconditioned with a tensile force of 5 N. The tensile cycle lasted 15 s and was performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…Graphene oxide (GO) can promote tissue repair by improving the physical properties of tissues. Bao et al (2021) prepared PRP gel containing different concentrations of GO to promote tendon-bone healing in rabbit tendon reconstruction model after RC injury. The results demonstrated that the addition of GO enhanced the biomechanical properties of the newly formed tendons and made the tendon-bone interface more stable.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…In another study, autologous platelet-rich plasma (PRP) gels, containing various concentrations of GO, were prepared to promote tendon–bone interface healing and supraspinatus tendon reconstruction in a rabbit model. Again, the incorporation of GO improved the ultrastructure and mechanical properties of the PRP gels [ 22 ]. GO also enhances the characteristics of biomaterials used for skin wound dressing and wound healing.…”
Section: Biomedical Applications Of Gomentioning
confidence: 99%